VIDEO SEBAGAI MEDIA KAMPANYE MANFAAT AIR KELAPA HIJAU MUDA UNTUK KESEHATAN TUBUH DI KOTA PALEMBANG - Fania Andriani; Mukhsin Patriansah; Bobby Halim (Penerbit dan Percetakan, CV. Picmotiv, 2023)
Abstract (10 pt): When you drink young coconut water, it is very fresh and has a sweet taste because it contains sugar. Apart from that, it has a number of macro and microminerals. Coconut water also contains vitamins and protein, although in small amounts. Young coconut water contains water protein, arginine, alanine, cysteine and serine, which are four types of high amino acids. Young coconut water contains a number of complete nutrients and is beneficial for body health. The nutritional content of young coconut water is protein, fat, carbohydrates, vitamin C, vitamin B complex, sugar, electrolytes and growth hormone. The types of sugar contained in young coconut water are sucrose, glucose, fructose and sorbitol. Designing a social campaign for the benefits of young coconut water for body health in Palembang City using video. By designing the video in this campaign, the author hopes that the public will know the many benefits of young coconut water for body health through the main media that will be designed by the author in the form of video motion graphics and supporting media such as calendars, books, posters, videos and branding. This campaign media will be made as attractive as possible so that people are interested in reading the information and education presented.